Protecting Student Intellectual Property in the Entrepreneurial Classroom. (April 2016) - Wright, Sarah L.; Katz, Jerome A.
While universities are intensely protective of revenue streams related to intellectual property interests for the institution and professors, the financial and legal interests of students in the entrepreneurial process have largely been overlooked. This lack of attention, both in universities and in the literature, is intriguing given the mushrooming growth in entrepreneurial education courses in almost every U.S. university. This article builds and reflects on an original article by Katz, Harshman, and Lund Dean where the authors advocate for establishing classroom norms for promoting and protecting student intellectual property. We present research, insights, and reflections from Professor Katz regarding the controversial ethical and legal issues related to student intellectual property in university settings and provide suggested resources for faculty traversing these issues.